2019
DOI: 10.1074/jbc.ra118.004885
|View full text |Cite
|
Sign up to set email alerts
|

Dual-reporter high-throughput screen for small-molecule in vivo inhibitors of plasminogen activator inhibitor type-1 yields a clinical lead candidate

Abstract: Edited by John M. DenuPlasminogen activator inhibitor type-1 (PAI-1) is a serine protease inhibitor (serpin) implicated in numerous pathological processes, including coronary heart disease, arterial and venous thrombosis, and chronic fibrotic diseases. These associations have made PAI-1 an attractive pharmaceutical target. However, the complexity of the serpin inhibitory mechanism, the inherent metastability of serpins, and the high-affinity association of PAI-1 with vitronectin in vivo have made it difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…To assess whether a small molecule inhibitor targeting PAI-1 could mimic the protection in Serpine1 -deficient mice, we used the newly developed inhibitor MDI-2268 (30), which increased the ratio of active to total tPA in vivo in both plasma and colon tissue (Fig. 5A and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether a small molecule inhibitor targeting PAI-1 could mimic the protection in Serpine1 -deficient mice, we used the newly developed inhibitor MDI-2268 (30), which increased the ratio of active to total tPA in vivo in both plasma and colon tissue (Fig. 5A and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5A and fig. S7A) (30). We administered this compound or a vehicle control to mice therapeutically on day 6, once mice began to lose weight from DSS-induced colitis.…”
Section: Pai-1 Inhibitor Therapy Reduces Severity Of Colitismentioning
confidence: 99%
“…These results revealed that uPA is critical for optimal wound healing and the accelerated wound healing observed after the administration of SPD. Recently, a novel inhibitor (MDI-2268) against PAI-1, which impairs the activation of uPA-uPAR signaling, was developed and proven effective in a mouse model of deep vein thrombosis [ 38 ]. In the present study, skin wound healing in systemic SPD-treated mice was significantly promoted by the administration of MDI-2268 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed that uPA is critical for optimal wound healing and the accelerated wound healing observed after the administration of SPD. Recently, a novel inhibitor (MDI-2268) against PAI-1, which impairs the activation of uPA-uPAR signaling, was developed and proven effective in a mouse model of deep vein thrombosis [33]. In the present study, we investigated the effect of MDI-2268 on wound healing in SPD-treated mice.…”
Section: Discussionmentioning
confidence: 99%